A systematic review of the nature of dispensing errors in hospital pharmacies - Aldhwaihi K; Schifano F; Pezzolesi C; Umaru N (Dove Medical Press, 2016)
Khaled Aldhwaihi, Fabrizio Schifano, Cinzia Pezzolesi, Nkiruka Umaru Department of Pharmacy, University of Hertfordshire, Hatfield, UK Background: Dispensing errors are common in hospital pharmacies. Investigating dispensing errors is important for identifying the factors involved and developing strategies to reduce their occurrence. Objectives: To review published studies exploring the incidence and types of dispensing errors in hospital pharmacies and factors contributing to these errors. Methods: Electronic databases including PubMed, Scopus, Ovid, and Web of Science were searched for articles published between January 2000 and January 2015. Inclusion criteria were: studies published in English, and studies investigating type, incidence and factors contributing to dispensing errors in hospital pharmacies. One researcher searched for all relevant published articles, screened all titles and abstracts, and obtained complete articles. A second researcher assessed the titles, abstracts, and complete articles to verify the reliability of the selected articles. Key findings: Fifteen studies met the inclusion criteria all of which were conducted in just four countries. Reviewing incident reports and direct observation were the main methods used to investigate dispensing errors. Dispensing error rates varied between countries (0.015%–33.5%) depending on the dispensing system, research method, and classification of dispensing error types. The most frequent dispensing errors reported were dispensing the wrong medicine, dispensing the wrong drug strength, and dispensing the wrong dosage form. The most common factors associated with dispensing errors were: high workload, low staffing, mix-up of look-alike/sound-alike drugs, lack of knowledge/experience, distractions/interruptions, and communication problems within the dispensary team. Conclusion: Studies relating to dispensing errors in hospital pharmacies are few in number and have been conducted in just four countries. The majority of these studies focused on the investigation of dispensing error types with no mention of contributing factors or strategies for reducing dispensing errors. Others studies are thus needed to investigate dispensing errors in hospital pharmacies, and a combined approach is recommended to investigate contributing factors associated with dispensing errors and explore strategies for reducing these errors. Keywords: dispensing errors, medication errors, hospital pharmacy, patient safety, contributing factors